Chapter 4. Evolutionary forces at work in fish populations - Santos, Jorge (Septentrio Educational, 2015)
This chapter of CONΣERV IT deals with the following questions in aquatic conservation: - How do escapees from aquaculture affect genetically salmon populations in rivers? - What are the time-scales of change in the gene pool of fish? - Can we eradicate undesirable traits from fish stocks? - Are small populations more or less affected by immigration? - What genetic diversity can we expect from large stocks in the sea? - How much, and how to avoid inbreeding in broodstocks used in fish farming? Population genetics migration selection deterministic Population genetics drift stochastic macro